2013
DOI: 10.1186/1471-2202-14-48
|View full text |Cite
|
Sign up to set email alerts
|

A neural extracellular matrix-based method for in vitrohippocampal neuron culture and dopaminergic differentiation of neural stem cells

Abstract: BackgroundThe ability to recreate an optimal cellular microenvironment is critical to understand neuronal behavior and functionality in vitro. An organized neural extracellular matrix (nECM) promotes neural cell adhesion, proliferation and differentiation. Here, we expanded previous observations on the ability of nECM to support in vitro neuronal differentiation, with the following goals: (i) to recreate complex neuronal networks of embryonic rat hippocampal cells, and (ii) to achieve improved levels of dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Our findings demonstrate that culture of NSCs within a hydrogel system supplemented with appropriate growth factors can maintain their stemness properties and could thus functions as a synthetic equivalent of the stem cell niche [34], [35]. Future studies using this system will allow analysis not only of the effects of the Shh signaling pathway on NSC, but also the specific source of this signal within the niche and how this and other signals collaborate.…”
Section: Discussionmentioning
confidence: 81%
“…Our findings demonstrate that culture of NSCs within a hydrogel system supplemented with appropriate growth factors can maintain their stemness properties and could thus functions as a synthetic equivalent of the stem cell niche [34], [35]. Future studies using this system will allow analysis not only of the effects of the Shh signaling pathway on NSC, but also the specific source of this signal within the niche and how this and other signals collaborate.…”
Section: Discussionmentioning
confidence: 81%
“…Recent evidence from a number of laboratories demonstrated that ECM proteins could have profound physiological effects on cells in vitro . In order to test the significance of varying ECM proteins on the behavior of cardiac myocytes, we examined the effects of the above‐mentioned four ECM proteins on hESC‐CMs.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to more conventional and easy-to-handle tumor or immortalized cell lines, which seem to grow on any kind of bare cell culture plastic. However, the extracellular matrix has also been shown to influence adhesion, proliferation, mobility, and morphology of rather robust cell lines (Fiegel et al, 2004;García-Parra et al, 2013;Liberio et al, 2014). For example, in the field of neuroscience, adhesion and neurite outgrowth of the pheochromocytoma cell line PC12 are highly dependent on the coating composition and coating procedures applied (Orlowska et al, 2017;Teppola et al, 2018).…”
Section: Recommendationsmentioning
confidence: 99%